2016
DOI: 10.1097/bsd.0000000000000359
|View full text |Cite
|
Sign up to set email alerts
|

Sacroiliac Joint Pain and Its Treatment

Abstract: The sacroiliac joint (SIJ) as a source of symptoms has been controversial; however, as knowledge about the joint increased, its role as a pain generator in patients complaining of symptoms that are often attributed to spinal pathology has become better appreciated. The literature reports that the SIJ is the pain origin in as many as 30% of patients presenting with low back pain. Clinically, the SIJ can be challenging to evaluate; however, assessing pain location, patient posture/movement, and provocative manua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 22 publications
2
75
0
16
Order By: Relevance
“…As a result of the strict definition, the SIJ group defined here consisted of ~20% of all patients in the current study. Some reports indicated that the proportion was 10%–30% 4,5,7. Therefore, our results were consistent with those of previous reports.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…As a result of the strict definition, the SIJ group defined here consisted of ~20% of all patients in the current study. Some reports indicated that the proportion was 10%–30% 4,5,7. Therefore, our results were consistent with those of previous reports.…”
Section: Discussionsupporting
confidence: 94%
“…LBP originating from SIJ dysfunction has been regarded as one non-specific cause of LBP 2. Some reports showed that the proportion of SIJ pain was 10%–30% of all LBP 4,5,7. There are no specific radiological findings, even on MRI, for the diagnosis of SIJ dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Visit frequency and duration should be determined by synthesizing clinical information such as the diagnosis, physical condition, care goals, intervention options, and expected response. Interventions: Education about the condition 13,[25][26][27][28][29]33,34 Spinal manipulation (thrust or non-thrust as tolerated) 10,13,[37][38][39] Heat, massage, low-level laser 37,38 Motor control exercise 37,38 General self-care and self-management advice 37,38 Consider recommending mindfulness-based stress reduction, tai chi, yoga, and progressive relaxation 37,38 Sacroiliac joint pain: Pain stemming from a sacroiliac joint 36 Interventions: Education about the condition 13,[25][26][27][28][29]33,34 Spinal manipulation 40 Regional muscle strengthening 41 Motor control exercise 37,38 Heat, massage, low-level laser 37,38 General self-care and self-management advice 37,38 Consider recommending mindfulness-based stress reduction, tai chi, yoga, and progressive relaxation 37,38 Discogenic pain: lumbar spinal pain, with or without referred pain, stemming from a lumbar intervertebral disk 36 Interventions: Education about the ...…”
Section: Consensus Statements: 6 Components Of Multimodal Chiropractimentioning
confidence: 99%
“…Из-за особенностей иннервации боль, связанная с неспецифическим патологическим процессом в илеосакральном сочленении, имеет многофакторный и комплексный характер [10][11][12]. по представленным в ряде исследований данным, боль неспецифического характера в крестцовоподвздошном суставе имеет место почти у 20% населения, она чаще встречается у лиц пожилого возраста без существенных гендерных различий [13][14][15][16].…”
Section: таблица 3 показатели цитокинового статуса и маркеров костнойunclassified